Unveiling a surprising diversity of the genus Diopatra Audouin & Milne Edwards, 1833 (Annelida: Onuphidae) in the Macaronesian region (eastern North Atlantic) with the description of four new species - Paxton, Hannelore; Arias, Andres (Zootaxa, 2017)
This study reviews previous records and reports on newly sampled species of the genus Diopatra from Macaronesia, a region comprising five volcanic archipelagos in the eastern North Atlantic Ocean. Of the three species previously known from the eastern North Atlantic and the Mediterranean, D. marocensis and D. micrura are newly reported from the Canary Islands, and the record of D. neapolitana from Madeira is confirmed. The earliest descriptions of Diopatra from Madeira are D. brevicirrus and D. madeirensis; the former is here considered as a nomen dubium, whilst the latter is redescribed, based on new collections from Madeira and the Canary Islands. Diopatra gallardoi, recently described from Namibia, is reported from the Canary Islands. Four new species are described: D. mariae sp. nov. and D. mellea sp. nov. with peristomial cirri (typical Diopatra), and D. budaevae sp. nov. and D. hektoeni sp. nov. (lacking peristomial cirri, previously considered as Epidiopatra); the former three species are from the Canary Islands and the fourth is from Cape Verde Islands. This brings the Diopatra fauna from the Macaronesian region to nine species. Diagnoses and full descriptions are presented for new and redescribed species and extended diagnoses for others, accompanied by detailed illustrations, including scanning electron micrographs and drawings. A dichotomous key to all recognized species is included plus a table summarizing specific diagnostic characters.